Health-related quality of life in patients with psoriatic and rheumatoid arthritis: data from the prospective multicentre NOR-DMARD study compared with Norwegian general population controls. Issue 9 (6th June 2018) - Michelsen, Brigitte; Uhlig, Till; Sexton, Joseph; van der Heijde, Désirée; Hammer, Hilde Berner; Kristianslund, Eirik Klami; Wierød, Ada; Bakland, Gunnstein; Rødevand, Erik; Krøll, Frode; Loge, Jon Håvard; Haugeberg, Glenn; et al.
Abstract : Objectives: To compare (1) Short Form-36 (SF-36) Physical Component Summary (PCS) and Mental Component Summary (MCS), scale scores and Short Form-6 dimensions (SF-6D) between patients with rheumatoid arthritis (RA) and patients with psoriatic arthritis (PsA) and Norwegian general population controls and (2) improvements in these measures between patients with RA and PsA. Methods: Analyses of covariance were performed to compare SF-36 measures between first-time enrolled patients with RA (n=3898) and PsA (n=1515) from the prospective observational multicentre NORwegian-Disease Modifying Anti-Rheumatic Drug study (6 months follow-up) and general population controls (n=2323). Results: In age and gender-adjusted analyses, patients with PsA compared with patients with RA had similar PCS, MCS and SF-6D (p≥0.14), worse vitality and general health, but better physical functioning at 0/6 months (p≤0.03). With additional 28-joint disease activity scores adjustment as a proxy for joint inflammation, PCS, most scale scores and SF-6D were worse in patients with PsA than patients with RA at 0/3/6 months (p≤0.01). PCS was more impaired than MCS both in RA and PsA compared with general population controls (p≤0.001). Mean 3-month and 6-month improvements after disease-modifying anti-rheumatic drug treatment were larger in patients with RA than patients with PsA for bodily pain, vitality and mental health (p≤0.02). Conclusions: Health-related quality of life was overall similar in patients with RA and patients with PsA—with a tendency to worse scores in PsA—and worse compared with Norwegian general population controls.